PENGARUH PROMOSI DAN KUALITAS PELAYANAN JASA PERBANKAN TERHADAP KEPUASAN NASABAH PADA PT. BANK RAKYAT INDONESIA UNIT PALMERAH JAKARTA - Rachmawan, Ade; Zakaria , Zakaria; Juanda, Angga (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
Customer satisfaction is an important target for every company that realizes the importance of service as the key to the company's operation as long as possible. From this customer satisfaction will arise customer loyalty that has been expected by all companies. BRI Unit Palmerah Jakarta is aware that promotion and service quality have an important role in creating customer satisfaction. BRI Unit Palmerah Jakarta must be more sensitive to see all customer needs, in order to meet customer needs according to customer expectations, because each customer certainly has different expectations regarding a quality of service. This study aims to find out how much influence promotion and service quality have on customer satisfaction of PT BRI Unit Palmerah. The method used is using a quantitative approach, namely analysis using statistical formulas to test the proposed hypothesis. Sugiyono (2013) explains that quantitative analysis is an analysis that is calculated in the form of numbers by determining statistical formulas to test the truth of theoretical data and hypotheses.